Spatio-temporal distribution of Dengue, Zika and Chikungunya in Cali, Colombia: 2014-2016 - José F. Fuertes-Bucheli; Gladys Pérez-Arizabaleta; Andrea Quiroz-Caicedo; Robin A. Olaya; Hoover O. León-Giraldo; Robinson Pacheco-López (Universidad y Salud)
Introduction: Emerging and re-emerging arboviral infections have become a public health challenge in the Americas due to their epidemic potential. Objective: To determine the spatio-temporal distribution of the dengue, Zika, and chikungunya viruses during an epidemic period in Cali, Colombia. Materials and methods: Multi-method descriptive ecological and exploratory study of confirmed and suspected cases reported to the epidemiological surveillance system between 2014 and 2016. Results: 40,168 cases were analyzed, and it was found that dengue was the most frequent arboviral infection (59.2 %). The most affected individuals were women (65 %) and those with a mean age of 34.5 years. Although arboviral infections spread out throughout the city, the three diseases were concentrated in significant groups located at the center-east and northeast areas of Cali (p<0.01; z=-203.7). Conclusions: This study identified critical zones for the three arboviral infections, which are located in areas with low socioeconomic status. Likewise, the results suggest that in addition to eco-epidemiological and bio-psychosocial factors, temperature, precipitation, and the aedic index may play an important role in the spatio-temporal behavior of these diseases. A multidisciplinary and collaborative approach is necessary, which must involve communities and authorities to implement effective control strategies, especially during epidemic periods.